2014
DOI: 10.1128/mcb.01503-13
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Functions of Human Cohesin-SA1 and Cohesin-SA2 in Double-Strand Break Repair

Abstract: Cohesin is an essential multiprotein complex that mediates sister chromatid cohesion critical for proper segregation of chromosomes during cell division. Cohesin is also involved in DNA double-strand break (DSB) repair. In mammalian cells, cohesin is involved in both DSB repair and the damage checkpoint response, although the relationship between these two functions is unclear. Two cohesins differing by one subunit (SA1 or SA2) are present in somatic cells, but their functional specificities with regard to DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
79
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(90 citation statements)
references
References 61 publications
10
79
1
Order By: Relevance
“…We found that only cohesin-SA2 stably associates not only with laser-induced damage sites, but also I-PpoI endonuclease-induced DSB sites (Fig. 3a ) [ 11 ]. Furthermore, depletion of SA2 (but not SA1) results in inhibition of sister c hromatid HR and stimulation of NHEJ [ 11 ].…”
Section: Cohesin Promotes Sister Chromatid Hr and Suppresses Nhej Andmentioning
confidence: 87%
See 3 more Smart Citations
“…We found that only cohesin-SA2 stably associates not only with laser-induced damage sites, but also I-PpoI endonuclease-induced DSB sites (Fig. 3a ) [ 11 ]. Furthermore, depletion of SA2 (but not SA1) results in inhibition of sister c hromatid HR and stimulation of NHEJ [ 11 ].…”
Section: Cohesin Promotes Sister Chromatid Hr and Suppresses Nhej Andmentioning
confidence: 87%
“…Based on our analysis of individual cells followed out of mitosis and into G1 phase prior to damage induction, we established that cohesin recruitment does not happen in G1 phase. This same cell cycle specifi city was confi rmed for both SMC subunits [ 14 ] and non-SMC subunits [ 11 ]. However, since the synchronization method used for ChIP analysis was serum starvation and release for ~10 h [ 24 ], we performed a longer time course analysis and found that some of cells in late G1 phase did begin to accumulate cohesin at DNA damage sites (data not shown).…”
Section: Cohesin Promotes Sister Chromatid Hr and Suppresses Nhej Andmentioning
confidence: 99%
See 2 more Smart Citations
“…The basis of these experiments is that the double-strand cleavage of DNA induces the cells' repair machinery to correct the damaged molecule. By the help of the subsequent processes (i) the shifted reading frame can be restored or a random mutation can be induced for gene knockout purpose by non-homologous end-joining, or (ii) a DNA of erroneous sequence -causing a genetic disease -can be corrected, or a gene can be inserted in a targeted way by homologous recombination in the presence of a suitable DNA template [12][13][14][15][16][17][18][19][20][21]. Because of this large scientific potential, there is a high demand of constructing specific artificial nucleases, as it is demonstrated by the continuously increasing number of publications on this hot topic.…”
Section: Introductionmentioning
confidence: 99%